The driving factors of E-loyalty marketplace customer: A structural equation modeling - Widayat Widayat; Marsudi Marsudi; Rahmad Wijaya; Fira Ibialty Kreatitin (Journal of Innovation in Business and Economics, 2022)
The research aims to determine the effect of webpage quality, Payment System, and E-satisfaction on the E-loyalty and E-satisfaction of E-Commerce customers. This research implied data from 180 Shoppe's E-commerce customers in Indonesia, selected using convenience sampling. Through Structural Equation Modeling (SEM), we showed that website quality and payment systems directly influence E-satisfaction and E-loyalty. E-satisfaction mediates the effect of website quality on E-loyalty but does not mediate the impact of the payment system on E-loyalty. This implies that E-commerce can cultivate customer E-loyalty by creating E-satisfaction that affects website quality and providing a convenient payment system to maintain customer loyalty.